Employability skills of business graduates in Saudi Arabia: Do academia and employers speak the same language? - Bindawas, Abdullah (Journal of Management and Business Education, 2024)
Graduate education plays a role in improving the scope for employability of graduates. It empowers them with specialized skills, advanced knowledge, and critical thinking, which increases the scope for their employability. However, in the case of Saudi Arabia, it has been reported that there is widespread unemployment in the country. Though the Saudi Arabian government has initiated measures to nurture development in education through their ‘Saudi Vision 2030’ program, a gap exists. There are strong indictors which point at a mismatch of knowledge and skills possessed by graduates in Saudi, and the requirements of the labour market. Therefore, this paper examines the apparent gap between academia and employers in terms of employability, while focusing on whether graduate students have the same set of skills that employers require. Using a review method, information was derived from secondary sources, mainly from papers having examined the same topic previously. From the findings, academia believed that the educational system needed an overhaul and economic diversification, with the creation of new employment opportunities. Though employers believed that Saudi graduates lacked soft skills impacting their employability. It was concluded that a collaboration between students and employers was required, where employers could offer inputs supporting graduate employability.